Оцінка знизу найкращих наближень періодичної сумовної функції двох змінних та спряжених до неї функцій через коефіцієнти Фур'є - Кононович, Т.О. (Український математичний журнал, 2008)
Установлены выраженные через коэффициенты Фурье оценки снизу суммы норм и суммы наилучших приближений тригонометрическими полиномами функций пространства L(Q²) и сопряженных по каждой и обеим переменным функций при условии их суммируемости. In terms of Fourier coefficients, we establish lower bounds for the sum of norms and the sum of the best approximations by trigonometric polynomials for functions from the space L(Q²) and functions conjugate to them with respect to each variable and with respect to both variables, provided that these functions are summable.